2020
DOI: 10.1002/celc.202001396
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of High‐Performance Organic Material Pyrene‐4,5,9,10‐Tetraone in Secondary Batteries

Abstract: Conjugated carbonyl electrode materials have attracted much attention because of their ability to store various cations, relatively high theoretical capacity, designability, and sustainability. In this Minireview, pyrene-4,5,9,10-tetraone (PTO) with four carbonyl functional groups served as the electrode material in secondary batteries. It exhibits excellent electrochemical performance, such as high theoretical specific capacity, high redox potential, and the high utility of active sites. Currently, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…[5][6][7] Compared with inorganic electrode materials, OEMs are gifted with wide sources of raw materials, outstanding theoretical specific capacity, mild synthesis conditions, designable structure and eco-friendly leading them to be one of the ideal electrode materials. [8][9][10][11][12][13] Although OEMs have many exciting advantages, their collocation with traditional organic liquid electrolytes (OLEs) did not get satisfactory results as we expected. The reason for this phenomenon is that OEMs are easily soluble in OLEs, causing the degradation of the capacity in organic secondary batteries (OSBs).…”
Section: Introductionmentioning
confidence: 78%
“…[5][6][7] Compared with inorganic electrode materials, OEMs are gifted with wide sources of raw materials, outstanding theoretical specific capacity, mild synthesis conditions, designable structure and eco-friendly leading them to be one of the ideal electrode materials. [8][9][10][11][12][13] Although OEMs have many exciting advantages, their collocation with traditional organic liquid electrolytes (OLEs) did not get satisfactory results as we expected. The reason for this phenomenon is that OEMs are easily soluble in OLEs, causing the degradation of the capacity in organic secondary batteries (OSBs).…”
Section: Introductionmentioning
confidence: 78%
“…The majority of commercial electrode materials are transition metal oxides, which are nonrenewable and damaging to the environment and do not meet the current concept of sustainable development. 1 The use of renewable and green organic compounds as electrode materials has been a hot topic in recent years. Organic molecules have the following advantages: high theoretical capacity, multiple active sites, structural tunability, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dissolution of PTO in common organic electrolyte causes a rapid decrease in capacity. 23 In order to suppress dissolution in electrolytes, many strategies were applied, including PTO immobilization in (porous) carbons, 7,24 electrolyte optimization, 25 changing polarity with introducing -CO 2 Li or -NO 2 groups (salt modifications), 26,27 and polymerization of PTO. 28−33 Modified PTO structures were employed in the designed cathode materials as the main chain, 30,34 side group, 28 or covalent organic framework (COF)/covalent organic polymer(COP).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pyrene-4,5,9,10-tetraone (PTO) has been widely used among the organic-carbonyl-based cathode active materials in recent battery studies. ,, PTO has four carbonyl groups as electrochemical active sites, resulting in high theoretical specific capacity (409 mAh·g –1 ) and high redox capacity. However, the dissolution of PTO in common organic electrolyte causes a rapid decrease in capacity . In order to suppress dissolution in electrolytes, many strategies were applied, including PTO immobilization in (porous) carbons, , electrolyte optimization, changing polarity with introducing -CO 2 Li or -NO 2 groups (salt modifications), , and polymerization of PTO. Modified PTO structures were employed in the designed cathode materials as the main chain, , side group, or covalent organic framework (COF)/covalent organic polymer­(COP). ,, Although one of the most used techniques to cope with the dissolution problem is the polymer formation, to the best of our knowledge only one study was reported in which polymethacrylate as a linear organic polymeric chain bearing PTO units was synthesized that exhibited the remarkable charge–discharge properties as a Li-ion cathode material .…”
Section: Introductionmentioning
confidence: 99%